Analysis Of China's Belt And Road Initiative (BRI) Policy In The Concept Of Balance Of Power - Nahar, Muhamad Akbar Yaumul (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
The Belt and Road Initiative (BRI) or better known as the "New Silk Road" is one of the Chinese government's economic and foreign policies, aimed at connecting Eurasian economies with infrastructure, trade and investment. The BRI policy consists of two main components: the Silk Road Economic Belt and the 21st Century Maritime Silk Road. China's Belt and Road Intiative (BRI) is a form of new economic power which in this case can be said to be the Image Community. Belt and Road Intiative (BRI) as China's effort to build hegemony in both the security and economic fields.